Makna Simbol Topeng Tengu dalam Anime Kimetsu no Yaiba karya Koyoharu Gotouge: Kajian Semiotika - Nugroho, Rahadiyan Duwi; Rizqu, Fauzan Afdhalul; Mirza, Muhammad (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 1 (2023), 2023)
The purpose of this research is to describe the meaning of the tengu mask symbol in the anime Kimetsu no Yaiba by Koyoharu Gotouge. The reason for this research is that at every opportunity to practice with his teacher, Tanjiro saw Urokodaki teacher always wearing a red tengu mask which was considered to have a certain meaning or symbol for Japanese society. This study uses a qualitative method. Data collection techniques in this study were obtained by observing and noting study techniques. Then, the data analysis technique uses descriptive techniques. Furthermore, the theory used is related to the relationship of signification by using Pierce's triadic triangle theory which consists of 3 elements, namely, representamen, interpretant and object. Next, the theory of trichotomous signs in the symbol section, the tengu mask and the theory of red color. The data source for this research is the anime Kimetsu no Yaiba. The results of the discussion are, the meaning of the symbol of the tengu mask in the anime Kimetsu no Yaiba by Koyoharu Gotouge, namely as a figure of a teacher or martial arts trainer who has a strong, firm, disciplined, humorous, humanist, wise, optimistic, and motivating character.